2006
DOI: 10.1096/fj.05-4879fje
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized tissue‐engineered chambers promote survival and function of transplanted islets and improve glycemic control

Abstract: We have developed a chamber model of islet engraftment that optimizes islet survival by rapidly restoring islet-extracellular matrix relationships and vascularization. Our aim was to assess the ability of syngeneic adult islets seeded into blood vessel-containing chambers to correct streptozotocin-induced diabetes in mice. Approximately 350 syngeneic islets suspended in Matrigel extracellular matrix were inserted into chambers based on either the splenic or groin (epigastric) vascular beds, or, in the standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The adipose tissue was found around mature vessels in addition to newly formed small vascular structures. In summary, these findings demonstrated that hyaluronic acid gel is applicable for generating adipose tissue in gels, displaying adipogenic as well as angiogenic properties, and strongly indicate its use as a matrix material for use as an injectable strategy for soft tissue reconstruction [34]. …”
Section: Adipose Tissuementioning
confidence: 99%
“…The adipose tissue was found around mature vessels in addition to newly formed small vascular structures. In summary, these findings demonstrated that hyaluronic acid gel is applicable for generating adipose tissue in gels, displaying adipogenic as well as angiogenic properties, and strongly indicate its use as a matrix material for use as an injectable strategy for soft tissue reconstruction [34]. …”
Section: Adipose Tissuementioning
confidence: 99%
“…Using this novel in vivo TE chamber, vascularized soft tissues including fat, muscle and connective tissues have been created [2][3][4][5]. In addition, a pancreatic organoid has been created by seeding adult mouse islets into the chamber, and the engineered islet graft effectively reduced blood glucose in type 1 diabetic mice [6]. Further, using neonatal rat cardiomyocytes in the rat chamber system, 3-dimensional strips of myocardial tissue have been created, which displayed contractions with intrinsic rhythms and could be paced, as well as producing positive chronotropic and inotropic responses in vitro to stretch, calcium and ␤-adrenoceptor agonists [7].Survival of the transplanted cells and the resulting tissue grafts in the TE chamber largely depends on the establishment of a functional vasculature capable of delivering sufficient oxygen and nutrients.…”
mentioning
confidence: 99%
“…It was later discovered that this ‘wound healing’ environment provides a highly intense environment of angiogenesis, which allowed various implanted cells to survive within it 98–100 . To date, using this intrinsic vascularization technique, constructs consisting of either hepatocytes, pancreas, 101 myoblasts, 99 adipose tissue 100 and CMs 20 have been engineered. Other groups have also used this model to engineer bone tissue 102,103 and a similar model in mice utilizing a pedicle flow‐through configuration has been developed, 104 which subsequently became the main model for adipose tissue engineering at our institute 100,105 …”
Section: Vascularization Strategies In Ctementioning
confidence: 99%